PENGARUH EMOTIONAL INTELLIGENCE (EI) TERHADAP PRESTASI BELAJAR AQIDAH AKHLAK SISWA KELAS VIII MTsN 1 LANGKAT - Anisa Khumaira Lubis (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2024)
This research focuses on discussing students' emotional intelligence, moral aqidah learning achievement and the influence of Emotional Intelligence (EI) on moral aqidah learning achievement of class VIII MTsN 1 Langkat students. This research uses a quantitative approach, which is a method used to answer research problems related to data in the form of numbers and statistical programs. The research respondents totaled 35 students. Data collection techniques were carried out by means of library research, observation, interviews, questionnaires and interviews. Hypothesis testing uses the product moment correlation formula. The results of the research explain that the influence of Emotional Intelligence (EI) has a positive and convincing contribution to class VIII MTsN 1 Langkat students and is categorized as very good 27 (77%). The learning achievement of moral aqidah of class VIII MTsN 1 Langkat students has been categorized as very good, 27 (77%). The influence of emotional intelligence contributes positively and convincingly to the moral aqidah learning achievement of class VIII MTsN 1 Langkat students, most of which are categorized as good with a moderate or sufficient level of significance, namely 0.561